ASPIRASI MAHASISWA TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM: KASUS MAHASISWA FIP UPI BANDUNG: THE STUDENTS’ ASPIRATIONS TOWARD THE ISLAMIC EDUCATION LEARNING AT UNIVERSITIES: CASE STUDY AT THE SCIENCE OF EDUCATION FACULTY AT INDONESIA UNIVERSITY OF EDUCATION (UPI) BANDUNG - Imran Siregar (Balai Penelitian dan Pengembangan Agama Jakarta, 2016)
This article presented the results of the research about Islamic education learning and the students’ aspiration tendencies. The case of the study was the students of the Science of Education Faculty (FIP) of Indonesia University of Education (UPI) by academic year 2015/2016. The research process had been runing for three months (October to December 2015). The results of research showed that the Islamic Education (PAI) learning at UPI conformed with the government policies and the principles of educational theories which aims to prepare the educator candidates whom according to the motto of UPI; scientific, educative, and religious.Through the multi domains of integrative learning approach that it was applied at UPI by some models and learning approaches awakened the students’ enthusiasms and developed their religious concepts and experiences more dinamically and openly. The PAI tutorials was not only in the classrooms but also in the mousque and at the Units of Students’ Activities which was supported by tutorial systems where all student has to follow it. Students’ aspirations to comprehend the religious sciences, to practiceit, and to obey it are believed to be achieved through the PAI learning system runing in UPI. Their worries just come from theirselves. According to them, the PAI learning had run well and comformed with their expectations. Keywords: Learning, Islamic education, university, UPI Bandung Tulisan ini menyajikan hasil penelitian tentang pembelajaran Pendidikan Agama Islam dan kecenderungan aspirasi mahasiswa. Penelitian ini mengambil kasus mahasiswa FIP UPI angkatan 2015/2016. Proses penelitian berlangsung selama tiga bulan (Oktober-Desember 2015). Hasil peneltian menunjukkan, bahwa pembelajaran Pendidikan Agama Islam (PAI) di UPI berjalan searah dengan berbagai kebijakan pemerintah dan prinsip-prinsip teori kependidikan yang bertujuan untuk mempersiapkan calon tenaga pendidik yang sesuai dengan motto UPI ilmiah, edukatif, dan religius. Melalui pendekatan pembelajaran integratif multi ranah yang diterapkan di UPI dengan berbagai ragam model dan pendekatan pembelajaran telah membangkitkan antusiasme mahasiswa dalam mengembangkan wawasan dan pengalaman keagamaan yang sangat dinamis dan terbuka. Perkuliahan PAI tidak hanya di ruang-ruang kuliah saja, tetapi juga di masjid dan UKM-UKM, dengan dukungan sistem tutorial yang wajib diikuti oleh seluruh mahasiswa. Aspirasi mahasiswa mendapatkan ilmu agama serta mampu mengaplikasikan dan menaatinya diyakini dapat tercapai melalui sistem pembelajaran PAI yang berjalan di UPI. Kekhawatiran mereka justru pada faktor internal diri mereka sendiri. Mereka menilai pembelajaran PAI telah berjalan sesuai dengan harapan dan keinginan mereka. Kata Kunci: Pembelajaran, Pendidikan Agama Islam, perguruan tinggi, UPI Bandung